THE IMPLEMENTATION OF INNOVATIVE LEARNING MODELS TOWARDS THE SKILL OF STUDENTS SCIENCE PROCESS ON PHYSIOLOGY CLASS - Supramono .; Rita Rahmaniati (LPPM Universitas Negeri Jakarta, 2017)
This study aimed to examine: (1) the influence of the implementation of inquiry model toward the skill of student science process of Biology Education students of Palangka Raya university, (2) the influence of PBM model toward the skill of student science process of Biology Education students of Palangka Raya university, (3) the influence of GI type cooperative learning toward the skill of student science process of Biology Education students of Palangka Raya university, (4) the difference of influence of inquiry model, PBM, GI toward the skill of student science process of Biology Education students of Palangka Raya university. The design of the research used of pretest and posttest control group design. The sample of the research was the students who take the plant physiology class. The data were collected by written tests and observations about the students' science processes. Unovariate of covariance analysis (anacova) was used in data analysis of learning outcome of science process. The research results showed that there are a significant influence of innovative learning models toward the student science process, which are of inquiry model of score F = 34.978; p = 0.000; PBM model of score F = 24.636; p = 0.000; and cooperative learning model of type inquiry group of score F = 9.361; p = 0.030.